2020
DOI: 10.1109/jstars.2020.3006270
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Lake Ice Phenology to Climate Change at Tibetan Plateau

Abstract: Lake ice phenology is a sensitive indicator reflecting global warming. In this paper, the long-term changes of lake ice phenology of the second largest lake at Tibetan Plateau (i.e., the Nam Co) in response to climate change are investigated based on mathematical modelling. The model has been testified capable of reproducing daily surface temperature of the lake in both frozen and unfrozen seasons. The lake ice phenology determined according to the simulated lake surface temperature is found consistent with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…In lakes with ice cover, LSWT has been rising and the duration of seasonal ice cover has been decreasing [109]. It has been shown in the literature that the average rate of decrease in lake ice cover duration shows an apparent agreement with the average rate of LSWT warming [55], [109], [298]. Guo et al (2020) investigated the long-term changes in lake ice phenology of Nam Co, the second largest lake on the Tibet Plateau and found that the rate of increase in LSWT minimum temperature of 0.12°C /a with warming of the AT during 1978-2017 was the main cause of its ice phenology changes, which resulted in a reduction in the duration of complete ice cover by 0.72 days per year, and predicted that the duration of complete ice cover would be reduced by 60 days if the AT warms by 2°C in the future [298].…”
Section: B Influence Of Lake Attribute Factors On Lswtmentioning
confidence: 96%
See 2 more Smart Citations
“…In lakes with ice cover, LSWT has been rising and the duration of seasonal ice cover has been decreasing [109]. It has been shown in the literature that the average rate of decrease in lake ice cover duration shows an apparent agreement with the average rate of LSWT warming [55], [109], [298]. Guo et al (2020) investigated the long-term changes in lake ice phenology of Nam Co, the second largest lake on the Tibet Plateau and found that the rate of increase in LSWT minimum temperature of 0.12°C /a with warming of the AT during 1978-2017 was the main cause of its ice phenology changes, which resulted in a reduction in the duration of complete ice cover by 0.72 days per year, and predicted that the duration of complete ice cover would be reduced by 60 days if the AT warms by 2°C in the future [298].…”
Section: B Influence Of Lake Attribute Factors On Lswtmentioning
confidence: 96%
“…Assuming that the lake is completely covered by ice, the heat exchange between air and water is blocked and the surface energy balance will be replaced by the land surface energy balance without the mixing depth of water. Based on this, Guo et al (2020) introduced the state of the lake (open water, ice cover, water and ice mixing) to modify the air2water model, which has 15 parameters (A2W-15) to be calibrated. It is worth noting that the model simulates a large bias in the very high/very low lake surface temperatures, which may be due to the uncertainty of the input model parameterization inheritance and the bias of the MODIS LST products [298].…”
Section: ) Physics-statistical Hybrid Model -Air2watermentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is very difficult to define the bounds of this surface layer [24]. Recently Guo et al [25] introduced a variant of air2water model with 15 parameters developed for thermal surface conditions of frozen lakes. Basing on the idea introduced in [25], in the present paper we propose a new version of air2water model that has 12 parameters but is much more flexible in capturing interrelationships between a cold or frozen lake surface, and the water body.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Guo et al [25] introduced a variant of air2water model with 15 parameters developed for thermal surface conditions of frozen lakes. Basing on the idea introduced in [25], in the present paper we propose a new version of air2water model that has 12 parameters but is much more flexible in capturing interrelationships between a cold or frozen lake surface, and the water body. The variant uses different parameterization for cold and warm water periods (basically, those with classical thermal stratification and inversion of water temperatures), and considers a situation of a mix of both of them.…”
Section: Introductionmentioning
confidence: 99%